Real wave packet and quasiclassical trajectory studies of the H++LiHreaction - Bulut, N.; Castillo, J. F.; Aoiz, F. J.; Banares, L. (Royal Soc Chemistry, 2008)
Time-dependent real wave packet (RWP) and quasiclassical trajectory (QCT) calculations have been carried out to study the H+ + LiH reaction on the ab initio potential-energy surface of Martinazzo et al. [J. Chem. Phys., 2003, 119, 11241]. Total initial state-selected and final state-resolved reaction probabilities for the two possible reaction channels, H-2(+) + Li and LiH + H+, have been calculated for total angular momentum J = 0 at a broad range of collision energies. Integral cross sections and thermal rate coefficients have been calculated using the QCT method and from the corresponding J = 0 RWP reaction probabilities by means of a capture model. The calculated thermal rate coefficients are found to be nearly independent of temperature in the 100-500 K interval with a value of approximate to 10(-9) cm(3) s(-1), which is in good agreement with estimates used in evolutionary models of early-Universe lithium chemistry. The RWP results are found to be in good agreement overall with the corresponding QCT calculations.
Keywords: Potential-Energy Surfaces; Early Universe; Cross-Sections; Reactive Scattering; Quantum Dynamics; Insertion Reactions; Lithium Chemistry; Rate Constants; Probabilities; System